Tamil drama in colonial Madras: the Parsi theatre connection. Issue 1 (2nd January 2021) - Hansen, Kathryn
ABSTRACT: Tamil musical theatre ( isai natakam ) became a thriving form of public entertainment in the late 19th and early 20th centuries. During this formative period, Parsi theatre companies from Bombay frequented Madras and staged Urdu-language spectacles before heterogeneous audiences. The legacy of historical contact between Tamil drama and Parsi theatre is visible at multiple levels: nomenclature, tale types, song genres, orchestration, troupe organization, use of the proscenium stage. The positive reception of Parsi theatre in Madras, however, was not a foregone conclusion, given the linguistic, social, and cultural boundaries to be crossed. Through an analysis of Parsi company performances, this essay shows the process of creating a multilingual theatrical public at the crossroads of urban Madras. It brings to light the patronage of an unsung sector, the community of Urdu-speaking Muslims clustered around the titular nawabs of Arcot. The sponsorship of the Begum of the Carnatic for a local troupe, the Madras Mahomedan Operatic Company, helped to disseminate the imported art, carrying it into wider networks of circulation.